A Review of Porous Concrete Pavement: Compressive Strength and Clogging Investigation - Amminudin, Ab Latif; Putra Jaya, Ramadhansyah; Doh, Shu Ing (Penerbit Akademia Baru, 2023)
Pervious concrete pavements (PCPs) have been widely accepted as a green infrastructure solution for urban areas. Currently, pervious concrete is commonly used in permeable pavement systems such as roadways, sidewalks, driveways, parking lots, and other light-duty flatwork applications. However, the main disadvantage of this type of pavement is that it loses permeability over time due to clogging and lower compressive strength due to the pore's structures. These critical issues are the topic of this review paper. Laboratory test results relevant to the compressive strength, clogging and maintenance are discussed in detail. This review aims to present a compilation of prominent findings of studies focused on compressive strength, clogging and maintenance of PCPs. Note that PCPs with higher compressive strength must be used on roads with high traffic volumes. Subsequently, periodic maintenance is necessary to prevent sediment clogging and maximise the life of PCPs. Based on this review paper, the area of need for future research are identified.